Club Drugs: Psychotropic Effects and Psychopathological Characteristics of a Sample of Inpatients - Martinotti, Giovanni; Negri, Attilio; Schiavone, Stefania; Montemitro, Chiara; Vannini, Chiara; Baroni, Gaia; Pettorruso, Mauro; De Giorgio, Fabio; Giorgetti, Raffaele; Verrastro, Valeria; Trabace, Luigia; Garcia, Andres; et al. (Frontiers in Psychiatry, 2020)
Background: growing evidence supports the possibility of significant psychiatric consequences related to novel and traditional psychoactive substance consumption. The problem of differential diagnosis has hampered research on specific psychopathologies with unclear outcomes. The aim of our study was to report psychiatric and clinical features of subjects admitted to a psychiatric ward in Ibiza, Spain, with a clinical diagnosis of substance abuse or intoxication. Methods: A survey was administered to a sample of inpatients hospitalized due to psychiatric symptoms related to recent use of psychoactive substances. The questionnaire investigated sociodemographic factors, familiar and personal anamnesis, substance use habits, general features and psychopathological features. Urine samples were collected and analysed in a toxicology laboratory using gas chromatography and mass spectrometry. Results: A total of 110 patients were included in the study. Most patients (70%) declared multiple substance use, and 33% of patients reported more than two substances; nevertheless, it was possible to identify 17 (15%) depressor users, 44 (40%) stimulant users and 49 (45%) psychodysleptics users. A positive association with a lifetime diagnosis of bipolar disorder was found (two-tailed Fisher’s exact test: p=0.013). Psychomotor agitation, reference and paranoid delusions, affective symptoms, consciousness disorders and aggressiveness represented some of the most frequent symptoms at entry evaluation. Conclusions: In this study, we described the acute psychiatric presentations related to recreational drug use in subjects on holiday in Ibiza. The use of psychoactive substances was characterised by poly-use of both traditional and novel substances, with several psychopathological consequences. Future research should focus on a better understanding of the psychopathological effects of specific substances, defining signs and symptoms to help make a differential diagnosis and prospectively examine long-term effects.